2000
DOI: 10.1007/s003940070002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet on the replenishment of intramyocellular lipids after exercise

Abstract: IMCL and glycogen can vary acutely in response to diet after exercise. Studies are needed to determine if such variations occur within the range of ordinary diets and to clarify the functional significance of IMCL in differently active individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 13 publications
1
51
0
Order By: Relevance
“…While the absolute level of IMCL concentrations is muscle-specific, a similar qualitative replenishment could be found (17). In a combined study of 1 H-and 13 C-MRS, Décombaz et al (36) were able to follow the replenishment of the two major energy supplies in skeletal muscle, IMCL and glycogen, under the influence of different diets. A well-controlled type of diet has been investigated in studies with the infusion of lipids and free fatty acids (54,(56)(57)(58).…”
Section: Various Other Influences Upon Imcl Levelsmentioning
confidence: 77%
See 3 more Smart Citations
“…While the absolute level of IMCL concentrations is muscle-specific, a similar qualitative replenishment could be found (17). In a combined study of 1 H-and 13 C-MRS, Décombaz et al (36) were able to follow the replenishment of the two major energy supplies in skeletal muscle, IMCL and glycogen, under the influence of different diets. A well-controlled type of diet has been investigated in studies with the infusion of lipids and free fatty acids (54,(56)(57)(58).…”
Section: Various Other Influences Upon Imcl Levelsmentioning
confidence: 77%
“…Boesch et al (2) revealed a decrease of IMCL in one subject performing a mountain bike ride over 3 h at about 70% of VO 2max , for the first time using 1 H-MRS to demonstrate that IMCL are metabolized during this form of exercise. In the following years, numerous reports on reduced IMCL levels during exercise were published and reviewed (17,20,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). It became obvious that both exercise duration and intensity are important factors in determining the reduction of IMCL (39).…”
Section: Various Other Influences Upon Imcl Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this technique, it has been found that IMCL levels are extremely variable in response to physical exercise 8,11,15,16 and diet. 8,17,18 It has also been shown that different muscle groups contain different levels of IMCL. 7,19,20 The role of IMCL in diabetes is not fully understood, however, an inverse correlation of IMCL levels and insulin sensitivity has been observed by several groups.…”
Section: Susceptibility Effects: Separation Of Imcl and Emclmentioning
confidence: 99%